Integrated FTA and FMEA for HDPE Plastic Bag Defect Reduction - Fitria Novi Ariestiyani; Rr. Rochmoeljati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Quality risk mitigation is essential for maintaining production stability and product conformity in manufacturing industries. Specific Background: PT XYZ produces High Density Polyethylene plastic bags in various sizes, with the 15×30 size exhibiting the highest defect rate during January–September 2025, particularly folded, incorrect cutting, asymmetrical cut, and no handle hole defects. Knowledge Gap: Previous studies generally applied Fault Tree Analysis (FTA) or Failure Mode and Effect Analysis (FMEA) separately or focused on limited defect types and specific production stages, resulting in less comprehensive defect evaluation. Aims: This study aims to systematically identify root causes and determine improvement priorities for dominant defects in 15×30 HDPE plastic bag production through an integrated FTA and FMEA framework. Results: FTA identified 15 critical basic events associated with operator control, machine condition, material handling, and maintenance practices. Defect probability values were 7.079% for folded, 9.314% for incorrect cutting, 9.741% for asymmetrical cut, and 6.635% for no handle hole defects. FMEA results showed the highest Risk Priority Number for folded defects (RPN 240), followed by incorrect cutting (RPN 210), asymmetrical cut (RPN 180), and no handle hole (RPN 175). Novelty: The study integrates deductive root cause modeling and quantitative risk prioritization within a single analytical structure applied to a specific industrial product size. Implications: The proposed actions, including SOP standardization, preventive maintenance, calibration, and operator monitoring, provide structured guidance for systematic defect reduction and sustainable quality management in HDPE plastic bag manufacturing. Highlights: Fifteen critical basic events were mapped across operator, machine, material, and maintenance factors. Incorrect cutting and asymmetrical cut showed the largest probability values among dominant nonconformities. Risk prioritization placed folded nonconformity at the top improvement rank based on RPN assessment. Keywords: Fault Tree Analysis, Failure Mode and Effect Analysis, HDPE Plastic Bags, Defect Probability, Risk Priority Number